PENGARUH PRENATAL YOGA TERHADAP TINGKAT STRES PADA IBU HAMIL : THE EFFECT OF PRENATAL YOGA ON STRESS LEVELS IN PREGNANT WOMEN - Indhun Dyah Susanti (LPPM STIKes Buleleng, 2025)
Introduction: Stress in pregnant women can increase the risk of pregnancy complications such as hypertension, premature labor, and fetal development disorders. Several studies have shown that prenatal yoga can help reduce stress levels, improve sleep quality, and strengthen mothers' mental readiness in facing childbirth. This study aims to determine the effect of prenatal yoga on stress levels in pregnant women Method: This study used a quasi-experimental design with a pre-post test design. The sample consisted of 30 pregnant women in the second trimester. The intervention was carried out during three prenatal yoga sessions. The measurement instrument used the Depression Anxiety Stress Scales (DASS). Data analysis used the Paired t-test. Result: The results showed a significant decrease in stress levels after prenatal yoga intervention (p <0.001). Conclusion: Prenatal yoga is effective in reducing stress levels in pregnant women in the second trimester.